Effects of Axillary Single-Port Incision Insufflation Endoscopic Breast-Conserving Surgery with Mini Latissimus Dorsi Surgery Versus Conventional Breast-Conserving Surgery - Luyang CHENG; Li LIU; Jiefang GUAN; Yangsu LAI; Lihan LIU; Hongdu ZHANG (Zhongliu Fangzhi Yanjiu, 2025)
ObjectiveTo compare the oncologic safety, surgical efficacy, and aesthetic outcomes between conventional breast-conserving surgery and axillary single-port incision insufflation endoscopic breast-conserving surgery with mini-latissimus dorsi surgery in early breast cancer patients. MethodsA retrospective analysis of clinical data from 62 female patients with early breast cancer was performed. Patients were divided into two groups on the basis of surgical method: the conventional group (37 cases) and the endoscopic group (25 cases).The clinical baseline data, surgical results, and postoperative effects of the two groups were compared. ResultsAccording to the clinical baseline data, the endoscopic group had a greater maximum tumor diameter and a greater tumor-to-breast volume ratio due to expanded indications for breast-conserving surgery (P<0.001), whereas the other data revealed no statistically significant difference between the two groups (P>0.05). Compared with those in the conventional group, the total incision length in the endoscopic group was shorter [3.40(3.15, 3.60) cm vs. 7.30 (6.50, 7.60) cm, P<0.001], the postoperative drainage volume was lower (206.20±35.11 ml vs. 223.95±26.17 ml, P=0.026), but the operative time was longer (254.92±22.67 min vs. 146.78±13.01 min, P<0.001). The incision margin positive rate was 0% (0/25) in the endoscopic group, which was significantly lower than the 10.8% (4/37) in the conventional group (P=0.141). The endoscopic group had a lower incidence of complications (4% vs. 27%, P=0.047) and superior JBCS aesthetic scores at the 6-month follow-up (76% vs. 43.2%, P=0.006). ConclusionAxillary single-port incision insufflation endoscopic breast-conserving surgery with mini-latissimus dorsi surgery is not inferior to conventional procedures in terms of oncologic safety (margin-negative rate) and offers advantages in terms of scar concealment, fewer complications, and better aesthetic outcomes, especially suitable for early breast cancer patients with small-to-medium breast volumes, tumors located in the outer quadrants and mastectomy ratios of >20%.